Autophagy and necroptosis in cisplatin-induced acute kidney injury: Recent advances regarding their role and therapeutic potential - Alassaf, Noha; Attia, Hala (Frontiers in Pharmacology, 2023)
Cisplatin (CP) is a broad-spectrum antineoplastic agent, used to treat many different types of malignancies due to its high efficacy and low cost. However, its use is largely limited by acute kidney injury (AKI), which, if left untreated, may progress to cause irreversible chronic renal dysfunction. Despite substantial research, the exact mechanisms of CP-induced AKI are still so far unclear and effective therapies are lacking and desperately needed. In recent years, necroptosis, a novel subtype of regulated necrosis, and autophagy, a form of homeostatic housekeeping mechanism have witnessed a burgeoning interest owing to their potential to regulate and alleviate CP-induced AKI. In this review, we elucidate in detail the molecular mechanisms and potential roles of both autophagy and necroptosis in CP-induced AKI. We also explore the potential of targeting either pathway to overcome CP-induced AKI according to recent advances.